SELF-MANAGEMENT IN LEARNING FOR BUDDHIS SMA TUNAS DHARMA KARAWANG - Nurcahya, Meta; Sukodoyo, Sukodoyo; Kiryono, Kiryono (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2023)
The purpose of study is to obtain an overview of Tunas Dharma Karawang High School Students’ self-management regarding studying. The research was conducted using decriptive qualitative method. Research data were collected by interview, observation, and documentation. The validity of the data was tested by diligent observation, triangulation, and member check. Data analysis is based on the Miles & Huberman model consisting of data collection, data reduction, data presentation, and drawing conclusions, as well as verification. The results of this research indicate that self-management in the learning of Buddhist students at SMA Tunas Dharma Karawang at the learning planning stage of students determines goals and plans learning strategy activities to be carried out. According to Buddhists, this is included in the four inner strengths (iddhipada), namely interest and satisfaction in doing the work. something that is the main factor in students to achieve maximum desired results (chanda). A passionate effort to achieve success in learning (viriya). Carrying out efforts to achieve success diligently and tenaciously by not abandoning or postponing the efforts being undertaken (citta). In carrying out learning, students pay attention to the lesson material, for example summarizing the lesson material, marking important sentences, seeking help from teachers and friends to understand the material (chanda and viriya). In learning evaluations, students evaluate their learning process and feel that their achievements or bad grades are caused by not being optimal in learning (vimaṁsā).